Between parental practices and values: children’s free will beliefs are associated with their parents' autonomy granting but not authoritarian values - Lee, Clyde Jing Yi (Nanyang Technological University, 2024)
The study explores the relationship between parental autonomy granting, authoritarian values, and children's beliefs in what they can choose to do or not do (free will beliefs) within Singaporean families. A total of 163 Singaporean children aged 4 to 10 and one parent each participated in an online study. Children’s beliefs in free will were assessed through scenario-based questions, while parents completed measures evaluating autonomy-granting behaviour and authoritarian values. Results revealed that children’s beliefs in free will was significantly correlated with parental autonomy granting but not authoritarian values. When including both predicters and control variables in a regression model, parental autonomy granting was also found to uniquely contribute to children’s free will beliefs after controlling for children’s age, children’s gender, and parents’ gender. These findings underscore the importance of autonomy granting in fostering children’s understanding of choice and whether they can choose to do something that they do not like or something that is hard for them within the socio-cultural context of Singapore. This study also highlights how the translation of values into day-to-day interactions may be pivotal in children’s development, as well as the need for culturally sensitive approaches to understanding parenting dynamics and child development.